Longitudinal diffusion imaging across the C9orf72 clinical spectrum. Issue 1 (20th October 2017) - Floeter, Mary Kay; Danielian, Laura E; Braun, Laura E; Wu, Tianxia
Abstract : Introduction: Discrepancies between diffusion tensor imaging (DTI) findings and functional rating scales in amyotrophic lateral sclerosis (ALS) may be due to symptom heterogeneity, particularly coexisting cognitive-behavioural dysfunction affecting non-motor regions of the brain. Carriers of expansion mutations in the C9orf72 gene, whose motor and cognitive-behavioural symptoms span a range from ALS to frontotemporal dementia, present an opportunity to evaluate the relationship between symptom heterogeneity and DTI changes. Methods: Twenty-eight C9orf72 mutation carriers with varied cognitive and motor symptoms underwent clinical evaluation and DTI imaging. Twenty returned for two or more follow-up evaluations. Each evaluation included motor, executive and behavioural scales and disease staging using the King's college staging system. Results: Widespread reduction of white matter integrity occurred in C9orf72 mutation carriers compared with 28 controls. The ALS Functional Rating Scale (ALSFRS-R) and King's stage correlated with DTI measures of the corticospinal tract and mid-callosum. Cognitive and behavioural scores correlated with diffusion measures of frontal white matter. King's stage, but not ALSFRS-R, correlated with anterior callosum DTI measures. Over a 6-month follow-up, DTI changes spread from anterior to posterior, and from deep to superficial subcortical white matter. In C9orf72 carriers with ALS or ALS-FTD, changes in corticospinal tractography measures correlated with changes in ALSFRS-R. Conclusion: Discrepancies between DTI findings and clinical measures of disease severity in ALS may partly be accounted for by cognitive-behavioural deficits affecting extramotor white matter tracts. Both ALSFRS-R and King's stage correlated with corticospinal DTI measures. Group-level DTI changes could be detected over 6 months.